(untitled) (Baghdad Science Journal, 2016)
This experiment was conducted to evaluate the effect of foliar spraying with gibberellic acid concentrations (0,50,100)mg.L¹ and proline acid concentrations (0, 25, 50)mg.L¹ and their interactions on some growth parameters of pea plant using clay pots in the botanical garden of Biology Department College of Education for pure science Ibn –Al-Haitham ,Baghdad University, for the growing season 2012-2013 the experiment involved the studing of some growth parameters as plant?s height, dry weight, wt. of pods.plant¹, biology yield and the concentration of some major elements (nitrogen, phosphorus and calcium) in plant?s seeds. The experiment was designed according to Completely Randomized Desig(CRD) with three replications. Results revealed that foliar application with the concentrations of both acid caused a significant increase in the growth parameters, and the interaction gave a significant effect, the concentration 100 mg.L¹ gibberellic acid and the concentration 50 mg.L¹ proline gave the best value for plant?s height, dry weight, the concentration of nitrogen and calcium in plant?s seeds, but the concentration 100 mg.L¹ gibberellic acid and the concentration 25 mg. L¹ proline acid gave the higheat value for the concentration of phosphorus in plant?s seeds while the concentration 50 mg .L¹ gibberellic acid and the concentration 25 mg.L¹ proline gave the best values for wt. of pods.plant¹, biology yield.